Assessing teachers’ systems thinking skills during a professional development program in Turkey - Ateskan, Armagan; Lane, Jennie F. (Journal of cleaner production, 2018)
Through effective professional development in Education for Sustainable Development (ESD), teachers can help students gain knowledge, skills, and dispositions to build and support sustainable communities. This paper shares how a university in Turkey developed, implemented, and evaluated an ESD professional development program (PDP) for in-service teachers. The evaluation focused on how the program enhanced participants’ awareness of thinking in systems. Thirty-nine teachers from different parts of the country participated. The PDP took place over eight months and was launched by a five-day summer workshop that included presentations, hands-on activities, and field trips. The theme of energy was used throughout the workshop to emphasize how the environment, society, and economy are connected and interdependent. Teachers’ systems thinking skills were analyzed through a pre- and post-workshop questionnaire and concept maps. Results of the questionnaire showed statistically significant differences between teachers’ systems thinking scale scores before and after the workshop. Concept map analysis, however, identified that participants need more support relating concepts such as social justice to the environment and economy.